Analisis Ketahanan Pangan pada Rumah Tangga Petani Padi Sawah di Nagari IV Koto Mudiek Kecamatan Batang Kapas Kabupaten Pesisir Selatan - Noli Susanti; Gusriati; Herda Gusvita (Jurnal Research Ilmu Pertanian, 2023)
The purpose of this study was to determine the level of energy and protein consumption in lowland rice farmer households in Regency and to determine food security in lowland rice farmer households in Nagari IV Koto Mudiek, Batang Kapas District, Pesisir Selatan Regency. viewed from the aspect of energy consumption and share of food expenditure. This research was carried out for one month, namely in June 2021. The location of the research was determined purposively, the data used were primary data and secondary data. The method used in this study is a quantitative descriptive method using research questionnaires. The results showed that the household energy consumption of lowland rice farmers in Nagari IV Koto Mudiek, Batang Kapas District, Pesisir Selatan Regency was 1969.84 kcal/capita/day or with an energy consumption level of 89.54%. Meanwhile, for household protein consumption of lowland rice farmers in Nagari IV Koto Mudiek, Batang Kapas District, Pesisir Selatan Regency, it is 58 grams/capita/day or with a protein consumption level of 100%. Household food security of lowland rice farmers in Nagari IV Koto Mudiek, Batang Kapas Kapas District, Pesisir Selatan Regency is as follows. (a) Food insecurity of 31 households (52.54%) (b) Food insecurity of 14 households (23.72%) (c) Lack of food in 4 households (6.77%) (d) Food insecurity as many as 10 households (16.95%).